2020
DOI: 10.1186/s12891-020-03776-3
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported outcome after patient-specific unicondylar knee arthroplasty for unicompartmental knee osteoarthritis

Abstract: Background Unicondylar knee arthroplasty was introduced in the late 1960s and remains a topic of controversial discussion. Patient-specific instruments and patient-specific implants are not yet the standard of care. The question remains whether this time-consuming and costly technique can be beneficial for the patient. The aim of this study was to evaluate whether a custom-made unicondylar knee arthroplasty leads to improved patient-reported outcome. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 50 publications
(53 reference statements)
0
12
0
Order By: Relevance
“…Of the remaining 30 articles, 13 were not relevant [6, 11, 17, 19, 21, 23, 26, 28, 29, 37, 39, 40, 43], one was a review [41], and one an in‐vitro study [44], which were all excluded after reading their full texts. This left 15 articles that were eligible for data extraction, of which six were on custom UKA [2, 13, 16, 22, 27, 45], six on custom BKA [3, 7, 33, 36, 42, 49], and three on custom PFA [9, 12, 38] (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the remaining 30 articles, 13 were not relevant [6, 11, 17, 19, 21, 23, 26, 28, 29, 37, 39, 40, 43], one was a review [41], and one an in‐vitro study [44], which were all excluded after reading their full texts. This left 15 articles that were eligible for data extraction, of which six were on custom UKA [2, 13, 16, 22, 27, 45], six on custom BKA [3, 7, 33, 36, 42, 49], and three on custom PFA [9, 12, 38] (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…One study [16] on custom UKA reported satisfaction rates of 88% “very satisfied”, 6% “satisfied”, and 6% “neutral” at 12–48 months (Table 3). Two studies on [33, 36] custom BKA reported satisfaction rates of 78–91% “satisfied”, 7–4% “neutral”, and 4–5% “dissatisfied” at 12–72 months A gait analysis study by Wang et al [49] revealed that, compared to OTS TKA, custom BKA enabled larger extensor moments at stance (0.63 versus 0.48 N m/kg, p < 0.05), greater peak extension torques (1.65 versus 1.37 N m/kg, p < 0.05), and larger internal knee rotation (6° versus 3°, p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations